(untitled) (Docentes 2.0 Journal, 2020)
The objective of this research was to propose the use of GeoGebra as a didactic resource aimed at the development of skills in the resolution of problems related to perimeter and area of ??flat figures, in the upper level of Basic General Education (BGE), in the area of ??Mathematics. This study was based on the advantages of GeoGebra when applied as a teaching resource. The focus of this research was mixed. The methodology was supported by documentary analysis, the application of a diagnostic test, a final test and surveys to diagnose the problem. The proposal consisted of the design of didactic sequences based on the use of GeoGebra. The implementation of the proposal was carried out in the 10th year of BGE in the Educational Unit "Ricardo Muñoz Chávez". Finally, in the evaluation of the proposal a comparative analysis of the results of the diagnostic test and the final test was performed. The results of the formative evaluation with the execution tasks were also analyzed. From the integration of the results, it was concluded that the students achieve a better performance in the skills involved in solving problems with perimeter and area.